Experimental studies on a swirling fluidized bed with annular distributor - Batcha, Mohd Faizal Mohideen; Raghavan, Vijay (2011)
This study reports the experimental findings on a swirling fluidized bed which operates with an annular-blade distributor. Spherical PVC particles (which fall under type D in Geldart's classification) with two different sizes (5.75 and 9.84 mm) were used as bed material to study different bed configurations, taking into account the variation of fraction of open area (12.9 and 17.2%), blade overlapping angles (9° and 12°) and bed weight (500 to 2000 g) for superficial velocities is from 1 to 7 m sec-1. The performance of the swirling fluidized bed was assessed in terms of pressure drop values, minimum fluidization velocity and fluidization quality by physical observation on regimes of operation. The most significant finding is that the pressure drop of the bed increased with superficial velocity after minimum fluidization, in contrast with a conventional fluidized bed. It was also found that the blade geometry has less effect on bed performance, compared to fraction of open area and particle size. New regimes of operation were discovered, and designated as wave regime and two-layer bed regime. The best configuration obtained in the current work, which provides stable swirling at lower pressure drops, is the one with 60 distributor blades and 12° overlapping angle, operating with 9.84 mm particles